2011
DOI: 10.1007/s00595-009-4253-9
|View full text |Cite
|
Sign up to set email alerts
|

Elective palliative resection of incurable stage IV colorectal cancer: Who really benefits from it?

Abstract: An elderly age tends to be a contraindication to an elective primary tumor resection in patients affected by incurable CRC. Massive lymph node involvement and mucoid adenocarcinoma should also be considered before planning major colonic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
2
9
1
1
Order By: Relevance
“…Of twenty-three full-text articles that were excluded, twelve had no comparator nonsurgical group [27][28][29][30][31][32][33][34][35][36][37][38] ; four used a non-resection group (that is, ostomy procedures) as comparators [39][40][41][42] ; and another four used patients who underwent curative surgery as the comparator group [43][44][45][46] . Two studies, each with four comparator groups, provided minimal information about those groups, and one had a patient population that overlapped with the population of another study included in the present review 14,47 .…”
Section: Study Selectionmentioning
confidence: 99%
“…Of twenty-three full-text articles that were excluded, twelve had no comparator nonsurgical group [27][28][29][30][31][32][33][34][35][36][37][38] ; four used a non-resection group (that is, ostomy procedures) as comparators [39][40][41][42] ; and another four used patients who underwent curative surgery as the comparator group [43][44][45][46] . Two studies, each with four comparator groups, provided minimal information about those groups, and one had a patient population that overlapped with the population of another study included in the present review 14,47 .…”
Section: Study Selectionmentioning
confidence: 99%
“…Controversy still exists concerning the patient who presents with advanced metastatic disease with an in situ primary tumor which itself provides very little in the way of symptoms. In these cases, most would still advocate primary excision where the response to neoadjuvant chemotherapy is a little unpredictable [111][112][113] and where there is a presumptive guess by the clinician of the likelihood of signi fi cant symptoms requiring semi-emergent surgery although the few studies available suggest that the likelihood of acute colorectal events necessitating urgent surgery are uncommon during the patient's life span [ 114 ] . Abstract Life expectancy has increased signifi cantly in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the geriatric assessment in adjuvant colon cancer should follow three steps: 113 10 Adjuvant Therapy of Colorectal Cancer in Older People…”
Section: The Geriatric Assessmentmentioning
confidence: 99%
“…Some researchers have demonstrated that primary colectomy results in improved overall survival in patients with otherwise unresectable metastatic colon cancer and have been strong advocates of a surgical approach. 7,8 However, opponents point out that resection of the primary tumor in metastatic unresectable cases can certainly delay chemotherapy. 6,9 Other research has suggested that multiagent cytotoxic and biologic chemotherapy treatment alone does not compromise survival and asymptomatic patients should be spared noncurative surgical resection.…”
mentioning
confidence: 99%